Trends in non-AIDS-related causes of death among adults with HIV/AIDS, Brazil, 1999 to 2010 - Erika Fazito; Ana Maria Nogales Vasconcelos; Maurício Gomes Pereira; Dilermando Fazito de Rezende (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2013)
The aim of this study was to analyze trends in the listing of non-AIDS-related causes of death on the death certificates of adults with HIV/AIDS in Brazil. The study analyzed mortality data for persons 15 to 69 years of age from 1999 to 2010. Standardized mortality odds ratios were used to compare mortality from non-AIDS-related causes in the group with HIV/AIDS listed on the death certificate and in the group without HIV/ AIDS. From 1999 to 2010, there were 6,120,670 deaths among adults in Brazil. Deaths in the HIV group represented 2.2% of the total. Non- AIDS-related causes, and more specifically cardiovascular diseases, diseases of the genitourinary system, and non-AIDS-related malignant neoplasms increased at higher rates in the group with HIV/AIDS listed on the death certificate. The results point to a greater increase in mortality from non-AIDS-related diseases among persons with HIV/AIDS. This finding suggests that long contact with HIV and antiretroviral therapy play an important role in the occurrence of these diseases.